2003
DOI: 10.1099/ijs.0.02521-0
|View full text |Cite
|
Sign up to set email alerts
|

Zooshikella ganghwensis gen. nov., sp. nov., isolated from tidal flat sediments

Abstract: Two red pigment-producing bacterial strains with a metallic green sheen were isolated from a sediment sample of getbol, the Korean tidal flat. Phylogenetic analysis based on 16S rDNA sequences showed that these isolates represent a phyletic lineage within the c-Proteobacteria that is distantly related to the genus Hahella. No bacterial species with validly published names showed ¢92 % 16S rRNA similarity with the getbol isolates. The strains were Gram-negative, chemo-organotrophic, aerobic and required NaCl (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 22 publications
1
46
0
1
Order By: Relevance
“…The clade's closest characterized relative (Fig. 3) is the free-living curved rod Zooshikella ganghwensis from tidal flat sediment in Korea (Yi et al, 2003).…”
Section: Prevalence and Phylogenymentioning
confidence: 99%
“…The clade's closest characterized relative (Fig. 3) is the free-living curved rod Zooshikella ganghwensis from tidal flat sediment in Korea (Yi et al, 2003).…”
Section: Prevalence and Phylogenymentioning
confidence: 99%
“…JE-34 (FJ595984) in the phylogenetic tree (Figure 4), this isolate was suggested as a member of a new species in the genus Zooshikella. This was mainly based on the pigment production which recently known that Zooshikella able to produce red and yellowish-red but not violet pigment (Yi et al, 2003;Lan et al, 2008;Kim et al, 2010). Further identification of SDPM1 isolate is undergoing in order to confirm this suggestion.…”
Section: Discussionmentioning
confidence: 75%
“…This organism was first isolated from the sea slug Elysia ornata collected in Japan in 2007 (Kurahashi & Yokota 2007 (Yi et al 2003). Although literature reports on E. elysicola are scarce, it has been identified in salmon suffering from PGI (Steinum et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 16S rRNA sequences indicated that the isolate constituted a new lineage in the gammaproteobacteria class, belonging to the order Oceanospiridalles, family Hahellaceae (Garrity et al 2005). The Hahellaceae family contains Endozoicomonas and 4 more separate genera: Hahella (Jeong et al 2005), Halospina (Sorokin et al 2006), Kistimonas (Choi et al 2010) and Zooshikella (Yi et al 2003). Although literature reports on E. elysicola are scarce, it has been identified in salmon suffering from PGI (Steinum et al 2009).…”
Section: Discussionmentioning
confidence: 99%